CHALLENGES IN TEACHING ENGLISH TO YOUNG LEARNERS IN IMPLEMENTING MERDEKA CURRICULUM - Anggiarima, Pritha (J-ELLiT (Journal of English Language, Literature, and Teaching), 2023)
The implementation of Merdeka Curriculum has made English to be included as local content at the primary school level. However, what has been designed on the national curriculum only sometimes goes by school implementation. This study focuses on teaching English in SDN Kidul Dalem 2 Malang, where English is taught as local content for grade 1 and 4 students, and highlights the hindrances. The researcher found that many students need more English exposure at home, do not have encouragement from their surroundings to learn English, and the materials in Merdeka Curriculum are sometimes too hard for the students.Keywords: Merdeka curriculum, challenges, young learners